2018
DOI: 10.1002/wrna.1475
|View full text |Cite
|
Sign up to set email alerts
|

Hfq chaperone brings speed dating to bacterial sRNA

Abstract: Hfq is a ubiquitous, Sm-like RNA binding protein found in most bacteria and some archaea. Hfq binds small regulatory RNAs (sRNAs), facilitates base pairing between sRNAs and their mRNA targets, and directly binds and regulates translation of certain mRNAs. Because sRNAs regulate many stress response pathways in bacteria, Hfq is essential for adaptation to different environments and growth conditions. The chaperone activities of Hfq arise from multipronged RNA binding by three different surfaces of the Hfq hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 150 publications
(466 reference statements)
6
131
0
Order By: Relevance
“…Two trans-encoded sRNAs who can silence target mRNAs through base pairing were found to be slightly enriched in BR-bodies ( crfA 0.67 and chvR 0.27) (Frohlich et al, 2018; Landt et al, 2010), while another was found to be slightly depleted ( gsrN -0.24) (Tien et al, 2018). Pairing of sRNAs with mRNAs typically occurs through the Lsm protein Hfq (Santiago-Frangos and Woodson, 2018; Vogel and Luisi, 2011), and we observe that 252/257 of these RNAs that associate with Hfq (Assis et al, 2019) are enriched in BR-bodies (Table S1).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Two trans-encoded sRNAs who can silence target mRNAs through base pairing were found to be slightly enriched in BR-bodies ( crfA 0.67 and chvR 0.27) (Frohlich et al, 2018; Landt et al, 2010), while another was found to be slightly depleted ( gsrN -0.24) (Tien et al, 2018). Pairing of sRNAs with mRNAs typically occurs through the Lsm protein Hfq (Santiago-Frangos and Woodson, 2018; Vogel and Luisi, 2011), and we observe that 252/257 of these RNAs that associate with Hfq (Assis et al, 2019) are enriched in BR-bodies (Table S1).…”
Section: Resultsmentioning
confidence: 86%
“…The exclusion of ribosomes from BR-bodies may also explain why long poorly translated mRNAs are enriched BR-body substrates. While eukaryotic RNA silencing machinery is found in P-bodies and stress granules (Hubstenberger et al, 2017; Jain et al, 2016), sRNAs were found to be enriched in BR-bodies (Fig 3A) and are known to base pair with mRNAs often through the RNA chaperone Hfq (Santiago-Frangos and Woodson, 2018; Vogel and Luisi, 2011). Indeed, Hfq bound RNAs identified by HITS-CLIP (Assis et al, 2019) including both mRNAs and sRNAs are enriched in BR-bodies (Fig S6, Table S1), suggesting mRNA silencing may be influenced by BR-body localization.…”
Section: Discussionmentioning
confidence: 99%
“…mainly at the distal face. Productive RNA interactions require the two RNA strands to physically associate, and the lateral rim of Hfq's ring of SBB domains appears to facilitate that process (Santiago-Frangos and Woodson, 2018;Sauer, 2013;Stanek et al, 2017). The SBB module also appears to enable oligomeric plasticity, including for various paralogs that form heteromeric assemblies or even for the very same protein (homomeric assemblies).…”
Section: Higher-order Assembly Of Sbbs Into Multimeric Ringsmentioning
confidence: 99%
“…This molecule binds to small RNA and is involved in elongating poly(A) tails and in stabilizing mRNA 47,48 . However, there is a possibility that hfq can induce mRNA decay by sRNA mediated regulation, which has been shown to be related to different growth conditions 49 . hfq was up-regulated (1.34-fold) at restricted DO thereby potentially enhancing rARU mRNA level, and down-regulated (−1.33-fold) at unrestricted DO possibly lowering rARU mRNA levels Cell wall binding motifs in rARU.…”
Section: Transcriptomic and Proteomic Response To Restricted And Unrementioning
confidence: 99%